Pokok-Pokok Pikiran Perbaikan Sistem Manajemen SDM PNS di Indonesia - Yeremias T Keban (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2004)
In the recentyears, as the result of reformation movement, there is an increaringpressure on the government side to reform their bureaucrats to fulfil the demand of the general public: to get better public services. To realise the public's demand, therefore, Indonesian government should reform their human resources management rystem in order to realise the creation of accountable, transparent, and responsive civil servant in Indonesia. To do so, in this article the author suggests that Indonesian government should adopt good governanceprincipks in managing their employees. How the adoption should be done has been described in greater detail through out this article.